Cannabis and Anxiety: A Critical Review - Alexander Beletsky; Cherry Liu; Bryson Lochte; Nebiyou Samuel; Igor Grant (Medical Cannabis and Cannabinoids, 2024)
Introduction: Cannabis has been reported to have both anxiogenic and anxiolytic effects. Habitual cannabis use has been associated with anxiety disorders (AD). The causal pathways and mechanisms underlying the association between cannabis use (CU)/cannabis use disorder (CUD) and anxiety remain unclear. We examined the literature via a systematic review to investigate the link between cannabis and anxiety. The hypotheses studied include causality, the common factor theory, and the self-medication hypothesis. Methods: Critical systematic review of published literature examining the relationship of CU/CUD to AD or state-anxiety, including case reports, literature reviews, observational studies, and preclinical and clinical studies. A systematic MEDline search was conducted of terms including: [anxiety], [anxiogenic], [anxiolytic], [PTSD], [OCD], [GAD], [cannabis], [marijuana], [tetrahydrocannabinol], [THC]. Results: While several case-control and cohort studies have reported no correlation between CU/CUD and AD or state anxiety (N = 5), other cross-sectional, and longitudinal studies report significant relationships (N = 20). Meta-analysis supports anxiety correlating with CU (N = 15 studies, OR = 1.24, 95% CI: 1.06–1.45, p = 0.006) or CUD (N = 13 studies, OR = 1.68, 95% CI: 1.23–2.31, p = 0.001). PATH analysis identifies the self-medication hypothesis (N = 8) as the model that best explains the association between CU/CUD and AD or state-anxiety. Despite the support of multiple large cohort studies, causal interpretations (N = 17) are less plausible, while the common factor theory (N = 5), stress-misattribution hypothesis, and reciprocal feedback theory lack substantial evidential support. Conclusion: The association between cannabis and anxiety is best explained by anxiety predisposing individuals toward CU as a method of self-medication. A causal relationship in which CU causes AD incidence is less likely despite multiple longitudinal studies suggesting so.